2007
DOI: 10.1002/chem.200601032
|View full text |Cite
|
Sign up to set email alerts
|

Tuning of the Structures of Chiral Phosphane‐Phosphites: Application to the Highly Enantioselective Synthesis of α‐Acyloxy Phosphonates by Catalytic Hydrogenation

Abstract: A family of new chiral phosphane-phosphites 5 has been prepared and employed in the synthesis of rhodium complexes of formulation [Rh(cod)(5)]BF4 (7). The use of bulky phosphane or phosphite groups in the preparation of 7 avoids the formation of undesired disubstituted complexes, one of which (9 a) has been isolated and characterized. Ligands 5 display important differences from the bulkier phosphane-phosphites 1: complexes 7-unlike their rigid [Rh(cod)(1)]BF4 counterparts-show fluxional behaviour in solution,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
28
0

Year Published

2008
2008
2012
2012

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 55 publications
(29 citation statements)
references
References 76 publications
1
28
0
Order By: Relevance
“…The few cases where such hybrid ligands were studied have proved inconclusive. Thus, for example, in the case of asymmetric hydroformylation, Pizzano and co-workers found that their PeOP ligands which combined both axial and P-stereogenicity were less selective than their ligands without P-stereogenicity, suggesting that the chiralities were not co-operative [4,5].Conversely, Buchwald and co-workers have reported significantly improved ees when their P-stereogenic binaphthyl substituted monophosphines were tested in palladium catalysed asymmetric vinylation and arylation reactions [6,7]. Previously our group have reported the novel synthesis of P-stereogenic MOP analogues ( Fig.…”
Section: Introductionmentioning
confidence: 96%
“…The few cases where such hybrid ligands were studied have proved inconclusive. Thus, for example, in the case of asymmetric hydroformylation, Pizzano and co-workers found that their PeOP ligands which combined both axial and P-stereogenicity were less selective than their ligands without P-stereogenicity, suggesting that the chiralities were not co-operative [4,5].Conversely, Buchwald and co-workers have reported significantly improved ees when their P-stereogenic binaphthyl substituted monophosphines were tested in palladium catalysed asymmetric vinylation and arylation reactions [6,7]. Previously our group have reported the novel synthesis of P-stereogenic MOP analogues ( Fig.…”
Section: Introductionmentioning
confidence: 96%
“…Thus, among the catalysts investigated, that derived from phosphane–phosphite 4 b produced excellent results, giving full conversion and affording 2 a with excellent chemo‐ and enantioselectivity (Table 1, entry 2). Interestingly, catalysts based on ligands 4 a and 4 b had low activity in the hydrogenation of related α‐acyloxyphosphonates 16b…”
Section: Methodsmentioning
confidence: 99%
“…[3,5-bis(trifluoromethyl)phenyl]phosphino}-(S)-1- [2-(diphenylphosphino) 6,53.7,122.8,123.1 (q,J = 271 Hz),125.7,127.6,128.5,128.6,128.9,129.5,130.7,130.9,131.1,131.8,131.9,133.7,133.9,134.1,144.0,144.2,149.7;: m/z = 761.1280, calcd for C 36 H 25 F 12 NP 2 (M + ): 761.1271. (3,5-difluorophenyl)phosphino]-(S)-1- [2-(diphenylphosphino) 2,45.9,59.8,125.1,126.5,126.9 (J = 271 Hz),127.4,128.4,128.5,128.6,128.7,129.1,133.7,133.9,134.1,134.7,134.9,135.5,135.7,140.8,148.9 3, 22.7, 59.9, 126.8, 126.9, 128.4, 128.5, 128.6, 128.8, 129.1, 131.8, 132.0, 132.7, 132.9, 133.8, 134.0, 137.6, 150.2, 150.5 7,59.8,122.8,123.2 (q,J = 271 Hz),126.2,127.8,128.5,…”
Section: General Procedures For the Preparation Of Phosphineaminophospmentioning
confidence: 98%
“…However, this does not mean that C 2 symmetry is essential for ligand design. In fact, the past decade has witnessed significant advancement in the use of unsymmetrical hybrid bidentate phosphorus ligands such as phosphine-phosphoramidite ligands, 6 phosphine-phosphite ligands 7 , and phosphine-aminophosphine ligands 8 for catalytic asymmetric hydrogenation. These types of ligands normally display excellent performance in a variety of asymmetric hydrogenations, comparable to or even higher than those obtained with C 2 -symmetrical ligands.…”
Section: Introductionmentioning
confidence: 99%